2013
DOI: 10.1017/s0031182012002107
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and analysis of a novel calcium-dependent protein kinase from Eimeria tenella

Abstract: The calcium-dependent protein kinases (CDPKs) are unique enzymes found only in plants, green algae, ciliates and apicomplexan parasites. In this study, a novel CDPK gene of Eimeria tenella, designed EtCDPK3, was cloned using rapid amplification of cDNA ends (RACE) based on the expressed sequence tag (EST). The entire cDNA of EtCDPK3 contained 1637 nucleotides encoding 433 amino acids and the deduced EtCDPK3 protein had canonical characteristic domains identified in other CDPKs, including a well-conserved amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…We also demonstrated the importance of EteIF3s7 in host cell invasion in invasion inhibition experiments. In our previous study, we showed that some anti-protein specific polyclonal antibodies reduced E. tenella sporozoites invasion in vitro (Han et al, 2013;Jiang et al, 2012b). In our current study, the reduced capacity of sporozoites preincubated with an anti-rEteIF3s7 polyclonal antibody to invade DF-1 cells demonstrated the importance of EteIF3s7 in host cell invasion.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We also demonstrated the importance of EteIF3s7 in host cell invasion in invasion inhibition experiments. In our previous study, we showed that some anti-protein specific polyclonal antibodies reduced E. tenella sporozoites invasion in vitro (Han et al, 2013;Jiang et al, 2012b). In our current study, the reduced capacity of sporozoites preincubated with an anti-rEteIF3s7 polyclonal antibody to invade DF-1 cells demonstrated the importance of EteIF3s7 in host cell invasion.…”
Section: Discussionsupporting
confidence: 61%
“…The gene expression profiles of the various developmental stages of Eimeria likely differ due to the different morphological characteristics and living environments required for the different stages of the life cycle (Han et al, 2010;Miska et al, 2004;Ng et al, 2002). Because sporozoites invade the epithelial cells lining the intestine, genes differentially expressed in sporozoites might be involved in host cell invasion (Han et al, 2013;Kinnaird et al, 2004;Wiersma et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that in vitro invasion inhibition assays reduced E. tenella sporozoite invasion with specific polyclonal antibodies [30], [31], [55], [56]. Western blots showed that rabbit anti-rEtPDIL antibody recognized a single band of the expected 24 kDa in E. tenella sporozoites, merozoites and sporulated oocysts, but not unsporulated oocysts.…”
Section: Discussionmentioning
confidence: 98%
“…The chicken embryo fibroblast cell line DF-1, derived from East Lansing Line (ELL-0) chicken embryos, was used for infection, inhibition assays and immunofluorescence experiments [30], [31]. Cells were infected at a ratio of one sporozoite per cell in complete medium (DMEM, Invitrogen, USA) containing 10% fetal calf serum (FCS) at 41°C.…”
Section: Methodsmentioning
confidence: 99%
“…[56][57][58][59][60][61][62] Studies on protozoans have shown that CDPKs are localized in the schizonts and pellicle in Plasmodium, in sporozoites in Eimeria, and also in the cilia and body of Paramecium. [63][64][65][66][67] CDPK3 is localized in the C. reinhardtii membrane-matrix fraction of the flagella. 19 Another 65 kDa CDPK has been shown to be localized in the C. moewusii flagella.…”
Section: Cdpk1 Is a Flagellar Membrane-matrix Proteinmentioning
confidence: 99%